Entrepreneurial Education in a Tertiary Context: A Perspective of the University of South Africa - Amadi-Echendu, Anthea Patricia; Phillips, Magaret; Chodokufa, Kudakwashe; Visser, Thea (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
South Africa is characterised by high unemployment levels, a low Total Early Stage Entrepreneurial Activity rate, and a high small business failure rate. Entrepreneurship and small business development is seen as a solution to end unemployment in South Africa. A study to understand how to improve small business support was conducted at the University of South Africa and has shown that alumni are unable to apply theoretical knowledge acquired from their studies. The purpose of this article is to explore the potential of the University of South Africa in becoming more entrepreneurial to address the aforementioned challenges. A desk study that reviewed literature was conducted to identify different constructs associated with an entrepreneurial university, namely entrepreneurial education, research and development, innovation, commercialisation and incubation, and stakeholders. In addition to traditional teaching methods, various alternative approaches can be used to stimulate entrepreneurial education to develop the skills of learners/students. To address these challenges a closer relationship between academia, government, and industry is paramount. It is recommended that universities incorporate entrepreneurial education in all their qualifications, expose students to on-the-job training, assist with the incubation of business ideas that students have, and provide a platform for cross-pollination of knowledge between industry, academia, and government.